A negative feedback loop underlies the Warburg effect - Jaiswal, Alok; Singh, Raghvendra (NPJ systems biology and applications, 2024)
Aerobic glycolysis, or the Warburg effect, is used by cancer cells for proliferation while producing lactate. Although lactate production has wide implications for cancer progression, it is not known how this effect increases cell proliferation and relates to oxidative phosphorylation. Here, we elucidate that a negative feedback loop (NFL) is responsible for the Warburg effect. Further, we show that aerobic glycolysis works as an amplifier of oxidative phosphorylation. On the other hand, quiescence is an important property of cancer stem cells. Based on the NFL, we show that both aerobic glycolysis and oxidative phosphorylation, playing a synergistic role, are required to achieve cell quiescence. Further, our results suggest that the cells in their hypoxic niche are highly proliferative yet close to attaining quiescence by increasing their NADH/NAD+ ratio through the severity of hypoxia. The findings of this study can help in a better understanding of the link among metabolism, cell cycle, carcinogenesis, and stemness.